E-commerce in agriculture: The case of crop protection product purchases in a discrete choice experiment - Wilm Fecke; Michael Danne; Oliver Mußhoff (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2018)
The internet is playing an increasing role in the development of rural areas. For farmers in particular, reliable internet access creates opportunities concerning farm management decisions. Hence, the goal of this study was to investigate German farmers' willingness to buy inputs online. Primary data was collected by conducting a discrete choice experiment about the purchase of crop protection products. Selection decisions of 165 arable farmers were analyzed by a generalized multinomial logit model (GMNL) resulting in willingness to accept (WTA) space estimation. WTA estimates show that farmers are willing to switch to an online merchant if they are offered a significantly lower price. However, word-of-mouth-reputation and consultation offered via traditional media do not influence farmers' WTA for an online merchant. In contrast, delivery time significantly affects farmers' WTA for inputs purchased online. We also show that farmers' risk attitudes, prior online shopping experiences, and education are influential factors for the WTA for an online merchant. Surprisingly, age and farm size do not impact farmers' WTA. Since e-commerce has not been widely established in agriculture yet, these results are of great practical importance. The findings of this study give online merchants of agricultural inputs a first orientation for choosing appropriate marketing measures. Moreover, results are interesting for education policy.
Keywords: 330; Internet use; E-commerce; Input purchasing; Online merchants; German farmers